Photodegradation of dichloroacetic acid and 2,4-dichlorophenol by ferrioxalate/H2O2 system - Pupo Nogueira, Raquel F. [UNESP]; Guimarães, José Roberto (Elsevier, 2000)
The photo-Fenton process using potassium ferrioxalate as a mediator in the photodegradation reaction of organochloride compounds in an aqueous medium was investigated. The influence of parameters such as hydrogen peroxide and ferrioxalate concentrations and initial pH, was evaluated using dichloroacetic acid (DCA) as a model compound under black-light lamp irradiation. An upflow annular photoreactor, operating in a single pass or recirculating mode was used during photodegradation experiments with artificial light. The extent of the release of chloride ions was used to evaluate the photodegradation reaction. The optimum pH range observed was 2.5-2.8. The efficiency of DCA dechlorination increased with increasing concentrations of H2O2 and potassium ferrioxalate, reaching a plateau after the addition of 6 and 1.5 mmol/L of those reagents, respectively. The total organic carbon (TOC) content in DCA and 2,4-dichlorophenol (DCP) solutions was compared with the chloride released after photodegradation. The influence of natural solar light intensity, measured at 365 nm, was evaluated for the dechlorination of DCA on typical summer's days showing a linear dependency. The photodegradation of DCA using black-light lamp and solar irradiation was compared.
Keywords: 2,4- dichlorophenol; Dichloroacetic acid; Fenton's reaction; Ferrioxalate; Photodegradation; Dechlorination; Dichlorophenol; Photoreactors; Total organic carbon (TOC); Acetic acid; Chemical reactors; Chlorine compounds; Composition effects; Dehalogenation; Hydrogen peroxide; Iron compounds; pH effects; Phenols; Photolysis; Solar radiation; Water treatment; 2,4 dichlorophenol; dichloroacetic acid; hydrogen peroxide; oxalic acid derivative; dechlorination; oxidation; photodegradation; priority journal; reaction analysis; sunlight